Histomorphology of the lymphoid tissues of broiler chickens in Kelantan, Malaysia - Mohd Zahirul Islam Khan; Mohd Masum; Md. Zubayer Ibna Khan; Abdur Rahman Aziz; Morsheda Nasrin; Mohd Nazmul Hasan Siddique; Mohd Mokhtar Arshad (Universiti Kebangsaan Malaysia, 2014)
The present research has been designed to understand the histomorphological development of lymphatic tissues of Cobb 500 strains of postnatal broiler chickens, aged between day old and D14 of Kelantan, Malaysia by gross and histological study. In the present study, it was found that the gross weight, length and width of the thymus, bursa of Fabricius and spleen were increased with the advancement of ages of the broiler chickens and was found higher from D14 to D28. Fine septa of connective tissue divide the thymus into lobes and lobules. The cortex of lobule is densely populated with lymphocytes. The bursal follicles were composed of a peripheral cortex which was rich in bursal cells and centrally depopulated medulla. The mucosal folds of the bursa were lined by pseudostratified columnar epithelium. The spleen has two compartments, the red and white pulp. The red pulp consisted principally of red blood cells, while the majority of the populations of white pulp were the lymphocytes. The histological mean length and width of the thymic lobules, bursal follicles and white pulp of the spleen were grown faster with the advancement of ages at D14 and D28. In conclusion, the increment of gross and histological parameters of lymphoid organs of broilers in the present study was due to aging of broilers.